Forest vector of the Siberian institute of higher education - G. S. Mironov; I. M. Danilin (Сибирский лесной журнал, 2020)
90-year history of the creation and development of the first forestry higher educational institution in Krasnoyarsk Krai – the Siberian Forest Institute / Siberian Institute of Forest Engineering / Siberian Institute of Technology / Krasnoyarsk State Academy of Technology / Siberian State University of Technology, currently – Reshetnev Siberian State University of Science and Technology. Information is presented on the main stages of the formation of the university, the directions of training forest specialists, and conducting scientific research.